2022
DOI: 10.1021/acsami.1c20698
|View full text |Cite
|
Sign up to set email alerts
|

Highly Luminescent and Stable Organic–Inorganic Hybrid Films for Transparent Luminescent Solar Concentrators

Abstract: Here, a highly luminescent, stable, and visible-transparent organic−inorganic hybrid film was in situ synthesized in a siloxane-polyether (di-ureasil) sol−gel process by dissolving a 4-hydroxy-2-methyl-1,5-naphthyridine-3-carbonitrile (2mCND) ligand and a europium(III) ion. Doping a europium(III) complex into di-ureasil achieves an boost in photoluminescence quantum efficiency (PLQY) from 23.25 to 68.9%. In particular, the excellent photostability of the hybrid film was demonstrated after a 15 h aging experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Recent studies have demonstrated that using inherently flexible siloxane-based hybrid materials effectively enhanced LSC performance and photostability. [23][24][25][26][27][28] These matrices are actually characterised by good visible transparency and thermo-mechanical, chemical and photostability, 29 and allowed the covalent attachment of a series of high QY fluorophores 30 aimed at improving the phase stability of the device with time. However, to the best of our knowledge, PCEs (η dev ) higher than 0.4% have not been reported for flexible matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that using inherently flexible siloxane-based hybrid materials effectively enhanced LSC performance and photostability. [23][24][25][26][27][28] These matrices are actually characterised by good visible transparency and thermo-mechanical, chemical and photostability, 29 and allowed the covalent attachment of a series of high QY fluorophores 30 aimed at improving the phase stability of the device with time. However, to the best of our knowledge, PCEs (η dev ) higher than 0.4% have not been reported for flexible matrices.…”
Section: Introductionmentioning
confidence: 99%
“…The luminescent self-healing materials synthesized by our team open potential applications in wearable devices, LED, solar cells, and self-healing electronics. [14][15][16][17]…”
Section: Introductionmentioning
confidence: 99%
“…Typically, LSCs consist of an optical waveguide embedded with luminescent uorophores, such as organic uorophores and quantum dots (QDs). [6][7][8][9][10][11] LSCs harvest incident sunlight and re-emit at a longer wavelength. The emitted light is transferred to edge-mounted PV cells through waveguided photoluminescence and total internal reection.…”
Section: Introductionmentioning
confidence: 99%